Comparative Dosimetric Analysis of Lung Cancer Treatment Planning for 3D-CRT Using 6 and 10 MV Photon Beams - Sumolmarl Worrapipat (2022)
Purpose: To compare the dosimetric results of planning target volume (PTV) and organs at risk (OAR) and to compare the quantitative analysis of PTV between 6 and 10 MV photon beams for lung cancer patients with 3DCRT treatment technique. Materials and Methods: Twelve non-small cell lung cancer patients who underwent 4D-CT scan at Division of Radiation Oncology, Siriraj Hospital between March 2009 and August 2011 were reviewed. The radiation oncologists delineated target volumes for each patients using Varian Eclipse Treatment Planning System, software version 8.6. The target volume was classified to gross target volume (GTV), clinical target volume (CTV) and planning target volume (PTV). Treatment planning was performed in PTV were projected on a free breath CT set. In PTV, the same exact beam arrangement was used with beam energies is 6 MV and 10 MV photons. The tumor prescription dose was 60 to 66 Gy in 2 Gy per fraction. For all plan, 95% of PTV should receive at least 60-66 Gy. An accepted maximum dose was 107 % of prescribed dose unless a higher maximum dose was located within PTV. Results: Statistical analysis of pair t-test showed that both energy 6 MV and 10 MV photon beams did not statistically significant effect on the maximum of radiation at significant level 05. The average the maximum of radiation dose on both energy 6 MV and 10 MV photon beams is 70.358 and 68.783 Gy. For the average radiation dose, there was no significant difference with average dose of radiation (p-value = 0.948), of 6 and 10 mv were 64.667 and 64.542. In addition, the effect of radiation dose for spinal-cord, dose for esophageal and dose for lung found the similar result. Both 6 MV and 10 MV photon beams didn’t effect on the dose for spinal-cord, dose for esophageal and dose for lung. (With statistically significant equal 0.934, 0.971 and 0.970, respectively). Dose for spinal-cord compared with an average of 42.250 Gy (6 MV) and 42.067 Gy (10 MV), dose for esophageal compared with an average of 24.567 Gy (6 MV) and 24.475 Gy (10 MV), and dose for lung compared with an average of 15.875 Gy (6 MV) and 15.808 Gy (10 MV). Conclusion: Using of high-energy 10-MV photon achieves the same tumor control as the 6-MV photon with acceptable complication rate as well as better saving for normal tissue, while generating negligible neutron dose equivalent. It is recommended that the choice to treat at 10 MV be taken as a risk versus benefit as the clinical significance remains to be determined on case by case basis.